LANGUAGE PROFICIENCY AND ACADEMIC EXCELLENCE: A STUDY OF INTERNATIONAL STUDENTS’ SUCCESS IN SINGAPORE - Benjamin , Yap Wei; Cheng, Olivia Lim (Research Journal of Health, Medicine and Nursing, 2024)
Singapore, a popular destination for international students, hosts a substantial number of non-native English speakers pursuing their education in a predominantly English medium environment. English language proficiency is a critical factor influencing the academic success of these students. This study explores the correlation between English language proficiency and academic performance among international students in Singapore. The Ministry of Education in Singapore invests significantly in scholarships and funding for international students, emphasizing the importance of student success